Legislasi Mahkamah Konstitusi dalam Putusan Mahkamah Konstitusi Nomor: 46/PUU-VIII/2010 di Tinjau dari Teori Hukum Hans Kelsen Tentang Konstitusi - Subroto Subroto (Justicia Islamica, 2014)
The legacy of the authority of the Constitutional Court (abbreviated as MK) is as follows: (1) to examine laws against the 1945 Constitution of the Republic of Indonesia; (2) to decide disputes over the authority of State institutions whose authority is granted by the 1945 Constitution of the Republic of Indonesia; (3) to decide on the dissolution of political parties; and (4) to decide disputes over the results of general elections. From the Constitutional Court's legislation, the author is interested in seeing the extent of the Constitutional Court's legislation in making a decision based on the legal theory put forward by Hans Kelsen, regarding the constitution. Kelsen's thinking encouraged the establishment of an institution called Verfassungsgerichtshoft or MK (Constitutional Court) which stands alone outside the Supreme Court, often called The Kelsenian Model. The Constitutional Court decision No. 46/PUU-VIII/2010 is a legal product issued by the Constitutional Court. From the decision, it will be analyzed with regard to the legal basis and legal considerations used by the Constitutional Court in deciding cases that are in accordance with the legal theory put forward by Hans Kelsen in his constitutional theory or not and about the legislation of the Constitutional Court in making the decision based on Hans Kelsan's legal theory.